FACTOR ANALYSIS OF CUSTOMER PURCHASE DECISION AT ESSPECTO COFFEE MANADO - Lengkey, Laura Verrent Katoce; Pandowo, Merinda H. C.; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This research was conducted at the Esspecto Coffee Manado. This study aims to analyze the factors that influence the customers purchase decision. This research used quantitative method. The data used are primary and secondary.  The sample studied was 100 respondents. The number of variables studied was 20 variables. After the data is processed by using factor analysis there is only 18 variables that can be analyzed further. The scale used is 7 points Likert scale. The data obtained from the respondents were processed using SPSS 20. The results showed that of the 18 factors analyzed by the factor analysis model, the factors influence by consumers in purchase decision at Esspecto Coffee Manado. These factors consist of 4 factors, namely Service Quality Index, Ambience and Amenities Rating, Facility and Value Perception, and Offering Quality and Brand Appeal.   Keyword: Customer Purchase Decision, Factor Analysis